Promotion of bone formation and antibacterial properties of titanium coated with porous Si/Ag-doped titanium dioxide - Zhao, Quanming; Wu, Jieshi; Li, Yankun; Xu, Ruisheng; Zhu, Xingyuan; Jiao, Yang; Luo, Rui; Ni, Xiaohui (Frontiers in Bioengineering and Biotechnology, 2022)
Implant materials are mainly used to repair and replace defects in human hard tissue (bones and teeth). Titanium (Ti) and Ti alloys are widely used as implant materials because of their good mechanical properties and biocompatibilities, but they do not have the ability to induce new bone formation and have no antibacterial properties. Through surface modification, Ti and its alloys have certain osteogenic and antibacterial properties such that Ti implants can meet clinical needs and ensure integration between Ti implants and bone tissue, and this is currently an active research area. In this study, bioactive Si and Ag were introduced onto a Ti surface by plasma oxidation. The surface morphology, structure, elemental composition and valence, surface roughness, hydrophilicity and other physical and chemical properties of the coating were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), a profiler and a contact angle meter (CA). Adhesion and extensions of osteoblasts on the surface of the material were observed by scanning electron microscopy, and proliferation and mineralization of osteoblasts on the surface of the material were observed by ALP staining and alizarin red staining. The antibacterial properties of the material were tested by culturing Staphylococcus aureus on the surface of the material. The osteogenic properties of Ti implants with porous Si/Ag TiO2 (TCP-SA) coatings were evaluated with in vivo experiments in rats. The results showed that Si and Ag were successfully introduced onto the Ti surface by plasma oxidation, and doping with Si and Ag did not change the surface morphology of the coating. The osteoblasts showed good adhesion and extension on the surfaces of Si/Ag coated samples, and the porous Si/Ag TiO2 coating promoted cell proliferation and mineralization. The bacterial experiments showed that the porous TiO2 coatings containing Si/Ag had certain antibacterial properties. The animal experiments showed that Si/Ag-coated Ti implants promoted integration between the implants and the surrounding bone. It was concluded that the porous Si/Ag TiO2 coating on the Ti surface had good osteogenic and antibacterial properties and provides an optimal strategy for improving the osteogenic and antibacterial properties of Ti implants.